Analysis of the Management Problems and Solutions to the Development of Modern Enterprises from the Perspective of Management Psychology - Wang, Xiaolan (Education Insights, 2026)
Management psychology is a discipline that explores the psychological processes and interactions between managers and employees, providing insights into behavior, motivation, and decision-making within organizational contexts. Its core principles and theoretical frameworks play a crucial role in modern business management, offering substantial practical value for enhancing organizational performance and sustaining competitive advantage. This study applies management psychology theories to systematically examine key challenges that constrain enterprise development, including gaps in management philosophy, inefficiencies in incentive systems, and limitations in team communication and collaboration. By integrating empirical observations and data-driven analysis, the paper identifies specific patterns of organizational behavior that hinder effective leadership and employee engagement. Drawing on established psychological models, the study proposes targeted interventions, such as optimizing motivational strategies, enhancing feedback mechanisms, and fostering adaptive team structures, aimed at improving managerial effectiveness and organizational cohesion. These recommendations provide actionable guidance for enterprises seeking to strengthen internal governance, enhance employee performance, and achieve sustainable business growth. The research not only contributes to the theoretical understanding of management psychology but also offers practical frameworks that can be directly applied to contemporary corporate operations, promoting long-term organizational resilience and efficiency.